Methodological Gaps in Left Atrial Function Assessment by 2D Speckle Tracking Echocardiography - Rimbaş,Roxana Cristina (2015)
Abstract The assessment of left atrial (LA) function is used in various cardiovascular diseases. LA plays a complementary role in cardiac performance by modulating left ventricular (LV) function. Transthoracic two-dimensional (2D) phasic volumes and Doppler echocardiography can measure LA function non‑invasively. However, evaluation of LA deformation derived from 2D speckle tracking echocardiography (STE) is a new feasible and promising approach for assessment of LA mechanics. These parameters are able to detect subclinical LA dysfunction in different pathological condition. Normal ranges for LA deformation and cut-off values to diagnose LA dysfunction with different diseases have been reported, but data are still conflicting, probably because of some methodological and technical issues. This review highlights the importance of an unique standardized technique to assess the LA phasic functions by STE, and discusses recent studies on the most important clinical applications of this technique.